Economic Dynamics and Local Wisdom in The Anyer Beach Tourism Area: An Ethnographic Study of Fishermen's Community Participation - Tia Atikah; Siti Nuraeni; Umayah Umayah; Ade Fathurohman; E Syarifudin; Deni Iriyadi (MASI Mandiri Edukasi, 2026)
This ethnographic study analyzes the economic dynamics and cultural resilience of the fishing community in Anyer Beach, a historic coastal area that has undergone profound transformation due to the tourism industry. The purpose of this study is to examine the pattern of livelihood transition from the traditional maritime sector to the service sector, measure the implications of emerging social disparities, and analyze how local wisdom practices are maintained amid the tide of commercialization. Ethnographic qualitative methods were used through participatory observation and in-depth interviews with various parties at the study sites, such as Kamasan Village and Sambolo 2 Beach. The results of the study show a radical transition in livelihoods driven by economic rationality, resulting in a significant surge in per capita monthly income (a wealth shock) of 400% to 900%. However, this rapid economic growth, supported by simple management, simultaneously triggered sharp social inequality and negative lifestyle changes. Culturally, local maritime wisdom, such as the Ruwat Laut ritual, demonstrated resilience, functional adaptation, and commodification as cultural tourism assets. It was concluded that Anyer's economic success was not yet supported by social and ecological sustainability. Therefore, an immediate transition to a structural co-management model, supported by a local regulatory framework, is recommended to more evenly and sustainably distribute tourism benefits.